A34 EFFECT OF AUTOPHAGY INDUCTION VIA TRPML1 ACTIVATION ON HEPATIC STEATOSIS. (15th March 2019) - Tersigni, C; Capurro, M; MacParland, S A; Selzner-Malekkiani, N; Jones, N
Abstract: Background: Extended criteria donors (ECD) are increasingly used to minimize the gap between available organs and liver transplant candidates. Steatotic liver grafts are a common type of ECD organs though they are often discarded as they are associated with poor transplant outcomes. Autophagy regulates lipid droplet (LD) accumulation in hepatocytes suggesting that altered autophagic function could be involved in the development of steatotic liver diseases. A lysosomal calcium channel, TRPML1, regulates autophagy via downstream TFEB activation and successive upregulation of autophagic and lysosomal gene expression. Therefore, we hypothesized that activation of TRPML1 via synthetic agonist ML-SA1 will attenuate hepatic steatosis by increasing autophagic flux and lysosomal function. Aims: The aims of the present study are to determine if:1)autophagic dysfunction contributes to steatosis, and 2)induction of autophagy via TRPML1 activation reduces hepatic steatosis in vitro . Methods: We established an in vitro fatty liver model by incubating a human hepatoma cell line (Hep3B cells) or isolated primary mouse hepatocytes with free fatty acids (FFA). LD accumulation was observed by BODIPY staining. To determine if autophagic flux was disrupted, Western blot (WB) for autophagy marker LC3II was performed in the presence of autophagy inhibitor, bafilomycin. To determine if TRPML1 was present and functional in Hep3B cells, cells were incubated with a bacterial toxin (VacA) that inhibits TRPML1 followed by incubation with ML-SA1. Cells were stained with LAMP1 and LC3II antibodies to visualize lysosomal and autophagy markers, respectively. WB was performed to measure levels of autophagy marker LC3II. Results: FFA treatment in Hep3B cells induced significant LD accumulation as assessed by BODIPY staining. WB for LC3II with bafilomycin showed that a 1mM FFA concentration activates autophagy, whereas a 1.5mM FFA concentration and above disrupts autophagy. Hep3B cells incubated with the bacterial toxin VacA, displayed features consistent with disrupted TRPML1 function including enlarged LAMP1-positive vacuoles and accumulation of the autophagy marker LC3II. ML-SA1 treatment reversed vacuolation and normalized LC3II levels. These findings suggest that in a hepatocyte cell line TRPML1 activation can restore lysosomal function and autophagic flux in toxin-treated cells. Conclusions: We determined that in an in vitro model of hepatic steatosis, progressive accumulation of lipids is associated with disrupted autophagic flux. Furthermore, since TRPML1 is functional in a hepatocyte cell line and can be activated by the agonist ML-SA1, we can determine if ML-SA1 decreases steatosis. These studies will determine if TRPML1 could be a potential therapeutic target for reducing steatosis in ex vivo graft perfusion models to improve fatty liver grafts. Funding Agencies: CCC